The income tax consequences of the in-house development of software - Hodge, Dominic Shaughn (Rhodes University, Faculty of Commerce, Department of Accounting, 2014)
The objective of this thesis was to explore the nature of expenditure incurred on the internal development of software and its treatment in terms of the accounting and taxation frameworks to which it is subject. In fulfilling the primary objective the thesis had a number of subsidiary considerations. These included, firstly, a brief analysis of the approach of the software industry in South Africa to the taxation treatment of this type of software. The second consideration was a discussion and analysis of the taxation framework which differentiates between capital and revenue and the extent to which the receipts produced by internally developed software may be informative of the nature of the expenditure. The third was an analysis of the deductibility of expenditure incurred in the production of software with the fourth analysing the tests employed in the determination of whether expenditure is capital or revenue in nature. The fifth objective was to briefly analyse the accounting standards which find application in the determination of whether or not the software created can be considered a capital asset. The final subsidiary objective of the thesis was an analysis of the taxation framework applicable to software in respect of research and development incentives, as well as the position in the United States of America. Throughout the thesis the most apparent commonality is that there exists a significant level of uncertainty as to the taxation treatment of software both in South Africa and in America. The research concludes by stating that such uncertainty is prejudicial to the interests of research and development in relation to software.
Keywords: Computer software -- Accounting; Income tax -- Data processing; Research and development projects; Income tax -- Law and legislation -- South Africa; Computer software -- Development -- South Africa; Computer software -- Law and legislation -- South Africa